The Gulliver syndrome: a conceptual framework to address therapeutic inertia in patients with borderline cardiovascular risk profiles - López-Gil, José Francisco; Abellán-Huerta, José; Abellán-Alemán, José (Frontiers in Cardiovascular Medicine, 2025)
We propose a novel clinical construct, the “Gulliver syndrome”, to describe the scenario in which multiple, mildly elevated cardiovascular risk factors (CVRFs) coexist within an individual and together result in a significantly heightened overall risk of cardiovascular disease (CVD). This accumulation of small deviations, often dismissed in clinical practice, can exert a synergistic impact on vascular health. Our aim is to formalize this underrecognized phenotype, which falls outside traditional diagnostic entities such as the metabolic syndrome, and to provide a framework that enables early recognition and management. We outline proposed diagnostic criteria, contrast this syndrome with related constructs, support its clinical relevance with emerging literature, and present a representative case. Ultimately, we advocate for this framework as a tool to overcome therapeutic inertia and encourage proactive, multifactorial interventions in primary and preventive care.